The Soweto Theatre music tuition programme: a community engagement and audience development programme of the Soweto Theatre - Nkosi, Absoluum David (My University, 2017)
Community Arts education development projects are some of the empowering initiatives that promotes Arts Education to the youth who had no opportunity to study the Arts as a school subject. These initiatives serve as vehicles to Democratise the Arts and to create equal education opportunities for those learners (youth) who attend government schools which do not offer basic Arts Education within their school curriculum (in South Africa, such schools are dominantly based in townships, urban periphery areas and rural areas). Therefore, these projects become critical extended community development education programs that empower the youth through Arts Education to acquire necessary knowledge needed to appreciate the Arts and to develop highly honed technical skills demanded by any Arts professional specialisation. In South Africa, patrons’ for community youth development Arts education programs includes the Departments of Arts and Culture, Departments of Community Development, Arts and Culture Institutions/Organisations, Commercial Businesses , Non-Government Organisations as well as private affluent individuals/family foundations. Soweto Theatre is a newly established (2012) professional first ever township based community Theatre in the South African history of community theatres’. As a municipality entity, it is meant to benefit its local and surrounding communities. Part of its community engagement activities includes the Music Tuition Program, which is set as its community youth Arts education development program. This research study investigates the experiences and challenges of Leadership, Management, Funding and Administration within the Soweto Theatre’s Music Tuition Program. Conclusions and recommendations drawn from this research study can aid existing struggling community arts education development programs to regain stability, and alert the ones that are still in their conceptialised stage to be aware of the common mistakes and adaptable working methods that must be considered for their strategic plans (to guarantee sustainability). Although this is a South African narrative, the findings could be informative to the global community development Arts education programs initiatives, whilst the recommendations could be adapted according to the different country’s respective sociocultural -economic and political context.
Research report submitted to Wits School of the Arts, University of Witwatersrand, in partial fulfilment of a Master’s degree in the field of Cultural Policy and Management, September 2017
Keywords: Music--Instruction and study--South Africa; Music in the theater